Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1515/cclm-2019-1146
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine-N-oxide (TMAO) determined by LC-MS/MS: distribution and correlates in the population-based PopGen cohort

Abstract: BackgroundAccumulating evidence indicates that trimethylamine-N-oxide (TMAO) may play a causal role in cardiovascular disease (CVD), chronic kidney disease (CKD) and type 2 diabetes (T2D). TMAO plasma concentrations show considerable intra- and inter-individual variation, underscoring the need for a reference interval in the general population to identify elevated TMAO concentrations.MethodsTMAO concentrations were determined using an LC-MS/MS assay in a community-based sample of the PopGen control cohort cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 39 publications
2
22
2
Order By: Relevance
“…Moreover, data collected in the current study did not support the hypothesis that TMAO is directly associated with CVD. We observed similar plasma TMAO levels in patients with confirmed angiographically CAD and control subjects with no medical history of CVD, and plasma TMAO concentration were coherent with values previously measured in the general population 27 . Moreover, no significant pure associations between the CETP genotypes and TMAO metabolism has been found.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, data collected in the current study did not support the hypothesis that TMAO is directly associated with CVD. We observed similar plasma TMAO levels in patients with confirmed angiographically CAD and control subjects with no medical history of CVD, and plasma TMAO concentration were coherent with values previously measured in the general population 27 . Moreover, no significant pure associations between the CETP genotypes and TMAO metabolism has been found.…”
Section: Discussionsupporting
confidence: 89%
“…27 studies were considered for this review [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Their major features such as study design, methodology used for TMAO determination, and the effects of foods on TMAO are given in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…15 studies evaluated the possible relationship between fish and TMAO. 13 studies demonstrated that levels of urinary or plasma TMAO and/or TMA are significantly associated with the intake of fish [ 11 , 12 , 20 , 21 , 24 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 36 ]. One of the earliest studies evaluated 46 different foods and demonstrated that only fish and other sea-products significantly increase urinary TMAO [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbiota modified by diet may also play a role in the relationships between acylcarnitines, phosphatidylcholine and cardiometabolic traits [ 35 , 36 ]. Numerous metabolites such as acylcarnitines and phosphatidylcholine, are involved in gut microbe–dependant pathways that contribute to the formation of hepatic production of trimethylamine-N-oxide (TMAO) from choline and sequentially into trimethylamine in the microbiota, which may increase risk of atherosclerosis [37] and glucose metabolism [ 36 , 38 ]. TMAO has been shown to play a causal role in cardiovascular disease via promotion of macrophage foam cell accumulation, leading to inhibition of the reverse cholesterol transport that affect aspects of bile and sterol metabolism, which in turn enhances platelet hyperactivity and initiates atherosclerotic plaque formation [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%